Do children prevent their poor old parents from working? - Ziwei Rao (ZBW - Leibniz Information Centre for Economics, 2021)
This study provides the first empirical evidence of the causal impact of fertility outcomes on old-age labor supply, by innovatively employing population policies in the early 1970s and the sex of the eldest child within families as plausibly exogenous instruments of fertility. The results show strong impact of children on preventing old parents from strenuous works at senior age, e.g. having one more child significantly reduces post-retirement aged rural parents' probability of working by 12.8 percentage points. Such impact is especially strong among the more vulnerable elder parents with worse health and little pension benefits. Furthermore, the results suggest that population policies might jeopardize the elderly well being by reducing family sizes and compelling old parents in bad health to continue working.
Keywords: I14; I18; J13; J26; 330; fertility; elderly labor supply; old-age support; health; pension